(untitled) - Saifutdinova, Z.A.; Babadjanova, Sh.A.; Kurbonova, Z.CH. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
To characterize the indicators of myelogram with impaired hemostasis in pregnancy. Materials and methods: The study investigated 17 pregnant women in the first trimester, who conducted cytological analysis of myelogram. Results: Inactive and nuclear megakaryocytes prevailed in the bone marrow in group of pregnant women with thrombocytopenia, indicating a violation of platelet production in bone marrow. There have not found significant changes in megakaryocytes into bone marrow and it prevailed megakaryocytes with platelets containing and platelets detached in groups with thrombocytopathies and coagulopathies. Conclusions: Myelogram indicators have been significant differences and great importance for the differential diagnosis of thrombocytopenia, thrombocytopathy and coagulopathy.